Analisis Tindakan Sosial Orang Tua Terhadap Penetapan Mahar - Putri Yani; Ibnu Phonna Nurdin; Zulfan Zulfan; Firdaus Mirza Nusuary; Bukhari Bukhari (Indo Publishing, 2026)
Acehnese wedding traditions place the dowry or jeulame as a symbol of honor, self-respect, and a form of responsibility from the man to the woman. However, in Gampong Ladang Tuha 1, there are no customary rules that specifically regulate the value of the dowry, so its determination is more influenced by family customs, social status, and the education level of the prospective bride. On the other hand, the annual surge in gold prices and differences in community economic conditions create a dilemma between following family customs, unwritten standards in society, or adapting to current social and economic conditions. This study aims to analyze the types of social actions of parents in determining the dowry in Gampong Ladang Tuha I based on Max Weber's theory of social action, which divides actions into four types: instrumental rationality actions, value-based actions, affective actions, and traditional actions. The research method used is a qualitative case study approach. Data were obtained through in-depth interviews, observation, and documentation techniques with ten informants, consisting of the Keuchik, four parents, and six young couples. The results show that there is a diversity of types of social actions of parents in determining the dowry. Some parents exhibit instrumental rationality, for example, setting a dowry based on the family's economic situation. Others base their actions on value rationality, such as setting a dowry based on educational background or religious values. Affective behavior is seen in parents who set a low dowry out of affection for their future daughter-in-law, while traditional behavior occurs when parents follow family customs without considering the family's economic situation.